Review on serious-education games for slow learners - Siti Nuraishah, Nazri; Tuty Asmawaty, Abdul Kadir; Siti Normaziah, Ihsan (Institute of Electrical and Electronics Engineers Inc., 2023)
Serious education games are popular as they engage and educate more learners, including slow learners who are normal students but have difficulty meeting academic standards. Having a game that targets a child's struggles can make a significant difference, helping them feel more confident. Our goal is to increase awareness of slow learners in the classroom and stimulate discussion about this population. This review identifies slow learners and examines serious games' advantages and features designed for them. The paper findings also explore whether these technologies can be more effective than traditional methods. Slow learners struggle with traditional teaching methods, so it's essential to find ways to make learning fun and exciting. This study shows that games designed for education provide children with a great learning experience. This is especially helpful for students who struggle with traditional education methods, especially slow learners. Serious games have been shown to benefit slow learners in a variety of ways. These include developing problem-solving skills, improving motivation and engagement, and increasing academic performance. Therefore, serious gaming strategies may be more effective than traditional methods of engaging slow learners. Research using serious games for slow learners should yield promising results.